Outpatient Clinical Trial in Dogs With Leptospirosis Treated With Enrofloxacin Hydrochloride-Dihydrate (ENRO-C) - Gutierrez, Lilia; Mendoza, Jesús; Rangel, Ana Bertha; Tapia, Graciela; Bernad, Maria Josefa; Sumano, Hector (Frontiers in Veterinary Science, 2019)
Pharmacokinetics of enrofloxacin HCl-2H2O (enro-C) in dogs and Monte-Carlo simulations vs. Leptospira spp, prompted a clinical study to treat the clinically apparent phase of this disease. Leptospirosis was diagnosed through real-time PCR from blood, micro-agglutination titers (MAT), clinical signs and liver and kidney blood parameters. For the purpose of determining clinical ability of participants to diagnose leptospirosis on first examination and to set an early treatment to avoid excessive organ damage, patients were clinically classified as: high-risk or medium-risk. Forty-five dogs were included in this trial (from year 2017 to early 2019). Treatment consisted of IM injections of a 5% aqueous suspension of enro-C (10 mg/kg/day) for 10 days, and thereafter enro-C was administered orally for 7 more days, in gelatin capsules. Thirty-four high-risk and 11 medium-risk dogs were treated including among them 6 puppies (4 high-risk aged 6 to 10 months, and 2 medium risk aged a mean of 6 and 7 months). Other ages ranged from 1 to 5 years. Fifteen cases had a history of having a previous treatment with other antibiotics, including all the puppies. Clinical diagnosis error was 13.5% (7/52 cases), and only one of the misdiagnosed dogs had been ranked as a high-risk patient. Three to 5 days after finishing treatment with enro-C, 82.2% of dogs were negative to real-time PCR from urine samples and 100% negativity was observed on day 30 after treatment, when antibody titers dropped to 1:100-1:200. Based on absence of clinical signs, real-time PCR and MAT titers, all treated dogs were considered treatment-success. In 6 to 24 months of clinical follow-up, no relapses were recorded. Adverse effects were inconsequential. This is the first report of successful treatment of canine leptospirosis utilizing a fluoroquinolone, and giving its efficacy, it is here suggested that enro-C is a viable choice to treat canine leptospirosis.